The “War on Terror” and the Principle of Distinction in International Humanitarian La (2010)
New security threats, which have surfaced in the past few years, are seriously jeopardizing the relevance and implementation of international humanitarian law. This paper investigates the impact of the war on terror on the principle of distinction in international humanitarian law, examining in particular whether the practices of some States, notably the US, have led to the emergence of new rules in relation to the principle of distinction. For this it looks at the principle from two separate, yet correlated, perspectives: a targeting and a detention perspective.